The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ma13245715
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Grain Boundary Misorientation on the Mechanical Properties and Mechanism of Plastic Deformation of Ni/Ni3Al: A Molecular Dynamics Study

Abstract: The effects of grain boundary misorientation angle (θ) on mechanical properties and the mechanism of plastic deformation of the Ni/Ni3Al interface under tensile loading were investigated using molecular dynamics simulations. The results show that the space lattice arrangement at the interface is dependent on grain boundary misorientations, while the interfacial energy is dependent on the arrangement. The interfacial energy varies in a W pattern as the grain boundary misorientation increases from 0° to 90°. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…The misorientation angle is defined as the difference between the crystallographic orientation of a single grain and its neighbors, which directly affects the grain structure, interface energy and mechanical properties of the grain boundary. The study showed that the mechanical properties of the grain boundary decrease with an increase in the angle of misorientation (Ding et al , 2020). The higher and lower rotation angles of the grain boundaries present in the different zones of the printed wall are displayed in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…The misorientation angle is defined as the difference between the crystallographic orientation of a single grain and its neighbors, which directly affects the grain structure, interface energy and mechanical properties of the grain boundary. The study showed that the mechanical properties of the grain boundary decrease with an increase in the angle of misorientation (Ding et al , 2020). The higher and lower rotation angles of the grain boundaries present in the different zones of the printed wall are displayed in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…The misorientation angle between adjacent grains of steels, has become one of the major concerns for the study of some mechanical and toughness properties of irons [1][2][3][4][5], carbon steel [3,6], stainless steel [7][8], other types of steels [8][9][10] and different alloys [11][12]. The misorientation angle play a big role for the propagation of cleavage fracture in steels and on the fracture surface appearance.…”
Section: Introductionmentioning
confidence: 99%